IMPLIKASI YURIDIS MENGENAI KEBIJAKAN PERLUASAN KOMPETENSI PTUN DALAM PENGUJIAN TINDAKAN FAKTUAL - Advento Jerenimo; Siti Mutmainah (Fakultas Hukum, Universitas Semarang, 2025)
The government has the task of realizing prosperity for the entire Indonesian nation, so it is necessary to intervene in all areas of life, which of course can give rise to clashes of interests which ultimately require The State Administrative Court to finish it. The absolute competence of the State Administrative Court in the State Administrative Law is to adjudicate State Administrative disputes, however, with the enactment of Law Number 30 of 2014 concerning State Administration (UUAP) bring about changes in the expansion of the practice of organizing State Administrative Courts in Indonesia, namely the testing of factual actions. The problems discussed in this study focus on the legal implications of the policy of expanding the competence of the State Administrative Court in testing factual actions after the UUAP came into effect. The approach method in this study is normative juridical, with qualitative data analysis. The results of the study indicate that the legal implications regarding the policy of expanding the competence of the State Administrative Court in testing factual actions after the enactment of the UUAP which is supplemented by Supreme Court Regulation Number 2 of 2019 concerning Guidelines for Settlement of Disputes over Government Actions and the Authority to Adjudicate Unlawful Acts by Government Agencies and/or Officials, transfers the authority of the District Court to adjudicate on the basis of a lawsuit under Article 1365 of the Civil Code to the State Administrative Court. However, the government's factual actions will not be questioned if there is no loss, considering that Article 53 paragraph (1) of the State Administrative Court Law requires an element of loss when filing a lawsuit against government actions. Abstrak Pemerintah mempunyai tugas untuk mewujudkan mewujudkan kesejahteraan bagi seluruh Bangsa Indonesia, sehingga perlu campur tangan dalam segala bidang kehidupan, yang tentu dapat menimbulkan gesekan kepentingan yang pada akhirnya membutuhkan Peradilan Tata Usaha Negara (PTUN) untuk menyelesaikannya. Kompetensi absolut PTUN dalam Undang-Undang Peratun adalah mengadili sengketa TUN namun dengan lahirnya Undang-Undang Nomor 30 Tahun 2014 tentang Administrasi Pemerintahan (UUAP) membawa perubahan perluasan terhadap praktik penyelenggaraan PTUN di Indonesia, yaitu pengujian tindakan faktual. Permasalahan yang dibahas dalam penelitian ini fokus pada implikasi yuridis mengenai kebijakan perluasan kompetensi Pengadilan Tata Usaha Negara dalam pengujian tindakan faktual pasca berlakunya UUAP. Metode pendekatan dalam penelitian ini adalah yuridis normatif, dengan analisa data kualitatif. Hasil penelitian menunjukan bahwa implikasi yuridis mengenai kebijakan perluasan kompetensi PTUN dalam pengujian tindakan faktual pasca berlakunya UUAP yang dilengkapi dengan Peraturan Mahkamah Agung Nomor 2 Tahun 2019 tentang Pedoman Penyelesaian Sengketa Tindakan Pemerintahan dan Kewenangan Mengadili Perbuatan Melanggar Hukum oleh Badan dan/atau Pejabat Pemerintahan, mengalihkan kewenangan Peradilan Negeri mengadili dengan dasar gugatan Pasal 1365 KUH Perdata ke PTUN. Namun tindakan faktual pemerintah tidak akan dipersoalkan jika tidak ada kerugian, mengingat dalam Pasal 53 ayat (1) UU PTUN, mengharuskan ada unsur kerugian ketika mengajukan gugatan atas tindakan pemerintah.